Removal of Phenol by Immobilization of Trametes versicolor in Silica–Alginate–Fungus Biocomposites and Loofa Sponge. Issue 2 (10th December 2015) - Carabajal, Maira; Perullini, Mercedes; Jobbágy, Matias; Ullrich, René; Hofrichter, Martin; Levin, Laura
Abstract : White‐rot fungi have potential in organic pollutant degradation. Immobilization of microorganisms has been successfully used for bioremediation. In this work, 25 isolates of Argentinean white‐rot fungi were tested for their tolerance toward up to 10 mM phenol in agar plates. Seven isolates were further evaluated for their ability to grow on plates with 2, 6‐dimethoxyphenol, gallic acid, 2, 4‐dichlorophenol, or guaiacol (7.5 mM), or with phenol as sole carbon source. Best results were obtained with Trametes versicolor, Irpex lacteus, Lentinus tigrinus, and Pleurotus lindquistii . The ability of immobilized cultures of T. versicolor BAFC 2234 to remove phenol, was studied. Silica‐alginate‐fungus biocomposites resulted in phenol removal (10 mM) of up to 48% (mainly attributable to biosorption) within 14 days. Immobilized on Luffa aegyptica, it removed between 62 and 74% of phenol (15 mM) in three repeated cycles over a period of 23 days. Laccase was the main oxidative enzyme detected, and the purified enzyme oxidized 84% of phenol (0.5 mM) in vitro within 4 h, while 43% was converted by a purified Mn‐peroxidase. The phenol phytotoxicity decreased noticeably. The concentrations of phenol removed are among the highest reported so far, thus this strain of T. versicolor may have good prospects for application in industrial wastewater treatment. Abstract : White‐rot fungi are screened for their ability to tolerate and degrade phenolic compounds. The best strain is immobilized in three different matrices to assess the potential use in further industrial continuous wastewater treatment applications. The selected Trametes versicolor immobilized in loofa sponge is removed between 62 and 74% of phenol (15 mM) under fed‐batch conditions. Its purified ligninolytic enzymes laccase and Mn‐peroxidase remove phenol in vitro.